What Teachers Believe : Mental Models about Accountability, Absenteeism, and Student Learning - Sabarwal, Shwetlena (World Bank, Washington, DC, 2018)
The time teachers spend teaching is low in several developing countries. However, improving teacher effort has proven difficult. Why is it so difficult to increase teacher effort? One possibility is that teachers are resistant to increasing effort because they do not believe their effort is suboptimal. Such beliefs may be based on their mental models on absenteeism, accountability, and student learning. This paper explores this idea using data from 16,000 teachers across eight developing countries, spanning five regions. It finds that, on average, teachers support test-based accountability and believe that they are in fact held accountable for student learning. In several countries, many teachers tend to normalize two types of suboptimal behaviors. These are (i) certain types of absenteeism, and (ii) paying extra attention to well-performing and well-resourced students. Finally, the paper shows that ideas of accountability and absenteeism are strongly framed by context in two direct ways. The first is whether teachers favor exclusively reward-based forms of accountability. The second is the degree to which they support absenteeism linked to community tasks. These results provide actionable insights on how changing teacher behavior sustainably might require reshaping underlying mental models.